Notes on ecology of wild goffin’s cockatoo in the late dry season with emphasis on feeding ecology - Berenika Mioduszewska; Mark O’Hara; Tri Haryoko; Alice Auersperg; Ludwig Huber; Dewi M. Prawiradilaga (Treubia, 2018)
Experimental work on captive Goffin’s cockatoos (Cacatua goffiniana) has highlighted the remarkable cognitive abilities of this species. However, little is known about its behavior in the natural habitat on the Tanimbar Archipelago in Indonesia. In order to fully understand the evolutionary roots leading to cognitively advanced skills, such as multi-step problem solving or flexible tool use and manufacture, it is crucial to study the ecological challenges faced by the respective species in the wild. The three-month expedition presented here aimed at gaining first insights into the cockatoos’ feeding ecology and breeding behavior. We could confirm previous predictions that Goffin’s cockatoos are opportunistic foragers and consume a variety of resources (seeds, fruit, inflorescence, roots). Their breeding season may be estimated to start between June and early July and they face potential predation from ground and aerial predators. Additionally, the observational data provide indications that Goffin’s cockatoos are extractive foragers, which together with relying on multiple food sources might be considered a prerequisite of tool use.